2014
DOI: 10.1103/physreve.90.042915
|View full text |Cite
|
Sign up to set email alerts
|

Universal Braess paradox in open quantum dots

Abstract: We present analytical and numerical results that demonstrate the presence of the Braess paradox in chaotic quantum dots. The paradox that we identify, originally perceived in classical networks, shows that the addition of more capacity to the network can suppress the current flow in the universal regime. We investigate the weak localization term, showing that it presents the paradox encoded in a saturation minimum of the conductance, provided the existence of hyper-flow in the external leads. In addition, we d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…We demonstrate that the transport of light in the low concentration sample behaves insensitive with respect to the incidence angle (internal reflection), as expected at diffusive regime, while the high concentration sample shows a decrease of optical conductance and an increase of absorption near the input border. We remark that this anomalous behavior of transport of light near the mobility edge with the internal reflection has been theoretically predicted by Ramos and co-workers in disordered electronic system [42] but never shown in optics. These results could open new avenues for the design and manufacture of more efficient photonic devices based on strongly disordered optical media.…”
supporting
confidence: 63%
See 2 more Smart Citations
“…We demonstrate that the transport of light in the low concentration sample behaves insensitive with respect to the incidence angle (internal reflection), as expected at diffusive regime, while the high concentration sample shows a decrease of optical conductance and an increase of absorption near the input border. We remark that this anomalous behavior of transport of light near the mobility edge with the internal reflection has been theoretically predicted by Ramos and co-workers in disordered electronic system [42] but never shown in optics. These results could open new avenues for the design and manufacture of more efficient photonic devices based on strongly disordered optical media.…”
supporting
confidence: 63%
“…The increase of localization with incidence angle near the input border could be also interpreted as that photons from superficial localized states that would be emitted by nonlinear effects (non-equilibrium) [43,55] can be again trapped in another superficial localized state, due to the increase of internal reflection. This latter implies in that the density and residence time (Q factor) of superficial localized states would increase as internal reflection (incidence angle) increases, which can be inferred from the theoretical predictions of Mirlin [39,40] and Ramos and co-workers [42] in disordered electronic media. Notice that an increase of the internal reflection with incidence angle would be remarkable, mainly for the coherently backscattered photons (previously localized), due to the enhanced refractive index that these photons would feel.…”
Section: Backscattering Experimentsmentioning
confidence: 81%
See 1 more Smart Citation
“…In [20] it was shown that while sending classical information over a network, the efcets of Braess paradox can be mitigated with access to quantum resources. In [21] Braess paradox was shown to occur in chaotic quantum dots.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical works covering this topic include universal fingerprints as the probability distributions of transmission eigenvalues and conductance [24][25][26][27][28], interference effects [29][30][31][32][33][34], entanglement [8,27,35,36], time-reversal symmetry breaking [25,28,[37][38][39] and phase coherence breaking or decoherence [40][41][42][43][44], which produce a large number of experimental fundamental consequences [5][6][7][8]. However, the analytical results are usually obtained in very specific regimes [5,6], motivating numerical studies of regimes beyond such analytical limitations and giving a deep understanding of electronic transport properties [26,28,36,38,45].…”
Section: Introductionmentioning
confidence: 99%